منهج الشيخ عبد الله بن زيد آل محمود في رعاية المصالح في الفتوى : دراسة تحليلية تقويمية - مري، صبيح محمد ماجد البريص
This thesis aims to shed light on the nonbinding legal opinions (Fatwas) of the noble scholar, scholar of Qatar, its jurist, its greatest judge, the declaimer of its largest mosque, the founder of its courts, the first president of its Shariah (Islamic law) courts and religious affairs, one of the nation’s prominent scholars, the trustworthy judge, the facilitator jurist, and the missionary preacher, Sheikh Abdullah bin Zaid Al Mahmoud - may Allah have mercy on him. In his Fatwas he took care of the interests of Muslims by providing them with easiness, mitigation, and clarification of the legitimacy of changing the Fatwa from time to time, as well as the importance of the correct Shariahbased Fatwa which revolves around Shariah and the evidence derived from it. He also clarified the importance of the Fatwa in all places and at all times, and provided the inference statement which is based on the evidence agreed upon from the Qur’an, the Sunnah, consensus, analogy, the differing evidence from the sayings of the companions, shariah of those before us, and the presumption of continuity (Istishab), custom, and blocking pretexts. The focus was on the main pivot of the research, which is the implementation of the evidence of unprescribed interests in the Fatwa without conflicting with the agreed upon the aforementioned evidence. To this end, the researcher addressed the Fatwas of Sheikh Abdullah bin Zaid Al Mahmoud – may Allah have mercy on him - due to the plentiful Fatwas of him in which he took care of the aspect of interest, using the inductive approach to collect the Sheikh’s sayings in which he considered the interest, clarification statement of its evidence, the researcher utilised the analytical approach to clear the dispute area in order to reach a preponderant jurisprudential opinion, if any. The researcher divided his research into four chapters. The first chapter presents the research plan and its general structure, the second chapter covers the biography of Sheikh Abdullah bin Zaid Al Mahmoud - may Allah have mercy on him, while the third chapter provides certification on the concept of Fatwa, its conditions, an explanation of the legality of changing a fatwa with a change in time and place, and the last chapter comprises the definition and explanation of diligence (Ijtihad), clarification of its conditions and divisions, as well as clarification on the extent to which the Sheikh - may Allah have mercy on him - possessed the tools of diligence. The researcher reached several important results which are: the implementing interest leads to the realisation of facilitation and easiness for Muslims, especially if it does not contradict with the evidence agreed upon, and the scholar must not be strict, nor should he make it difficult for Muslims. The implementation also assists in achieving the objectives of Shariah in Fatwa by protection of religion, protection of intellect, life, property, and honor, as well as clarifying the religion tolerance, the easiness and benevolence of the Shariah of Islam.